PENGARUH PENGAWASAN, KOMPETENSI KERJA DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PADA PT. ALFA SCORPII CABANG BINJAI - Calvina Dwi Kolim; Hendra Nazmi; Edria Jesslyn Tania; Cynthia Chandra (JURNAL MANAJEMEN, 2020)
The purpose of this study was to determine the effect of supervision, work competence and work stress on employee performance at PT. Alfa Scorpii Binjai Branch. The population and sample in this study were 62 employees. The research method used is multiple linear regression analysis. The results of statistical analysis testing partially the supervision has a positive and significant effect on employee performance at PT Alfa Scorpii Binjai Branch. Partially, competence has a positive and significant effect on employee performance at PT. Alfa Scorpii Binjai Branch. Partially, work stress has a positive and significant effect on employee performance at PT. Alfa Scorpii Binjai Branch. Simultaneously supervision, work communication and work stress have a positive and significant effect on employee performance at PT. Alfa Scorpii Binjai Branch.